2012
DOI: 10.1016/j.molcel.2012.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Alternative Splicing Provides a Mechanism for the Regulation of MicroRNA Processing in Arabidopsis thaliana

Abstract: MicroRNAs (miRNAs) have emerged as a class of regulators of gene expression through posttranscriptional degradation or translational repression in living cells. Increasing evidence points to the important relationship between miRNAs and environmental stress responses, but the regulatory mechanisms in plants are poorly understood. Here, we found that Arabidopsis thaliana intronic miR400 was cotranscribed with its host gene (At1g32583) and downregulated by heat treatment. Intriguingly, an alternative splicing (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
180
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(188 citation statements)
references
References 55 publications
2
180
0
Order By: Relevance
“…Alternative splicing has recently been implicated as playing a major role in these processes during stresses, including disease, heat, drought, and others (Deom et al, 1987;Iida et al, 2004;Jeong et al, 2011;Kakumanu et al, 2012;Chang et al, 2014;Mandadi and Scholthof, 2015). Gene expression changes in splicing factors are a major factor in determining stress-induced alternative splicing changes (Yan et al, 2012;Leviatan et al, 2013;Staiger and Brown, 2013). For example, Cui et al (2014) recently showed that overexpression of the splicing factor SAD1 conferred increased splicing precision and resulted in increased tolerance to salt stress in Arabidopsis (Arabidopsis thaliana).…”
mentioning
confidence: 99%
“…Alternative splicing has recently been implicated as playing a major role in these processes during stresses, including disease, heat, drought, and others (Deom et al, 1987;Iida et al, 2004;Jeong et al, 2011;Kakumanu et al, 2012;Chang et al, 2014;Mandadi and Scholthof, 2015). Gene expression changes in splicing factors are a major factor in determining stress-induced alternative splicing changes (Yan et al, 2012;Leviatan et al, 2013;Staiger and Brown, 2013). For example, Cui et al (2014) recently showed that overexpression of the splicing factor SAD1 conferred increased splicing precision and resulted in increased tolerance to salt stress in Arabidopsis (Arabidopsis thaliana).…”
mentioning
confidence: 99%
“…Intronic miRNAs can be subject to inefficient splicing or alternative splicing which can affect the miRNA production. Expression of intronic miR400 is downregulated by heat treatment due to an alternative splicing event which causes the miRNA to be retained in the host gene [49]. To investigate miRNA origins, we first added introns to the barley annotation file from the International Barley Sequencing Consortium (ftp://ftpmips.helmholtz-muenchen.de/plants/barley/ p u b l i c _ d a t a / g e n e s / b a r l e y _ H i g h C o n f _ g e n e s _ MIPS_21Aug12_Transcript_and_CDS_structure.gff) using Genome Tools (version 1.4.1) and converted the .gff file into .bed format.…”
Section: Origins Of Predicted Mirnasmentioning
confidence: 99%
“…Until now, 12 intronic miRNAs have been found in the genome of Arabidopsis thaliana. 37,38 Our bioinformatic and experimental studies revealed that 17 more miRNAs of A. thaliana are also encoded within introns of protein -and noncoding genes (manuscript in preparation). Thus, in the A. thaliana genome approximately 8% of miRNAs are encoded within introns of host genes, while the remaining represent independent transcriptional units.…”
mentioning
confidence: 99%
“…17,18,39,40 These introns undergo complex alternative splicing, providing a possible mechanism for the regulation of miRNA processing in A. thaliana. 38,41 Our estimations have shown that approximately 50% of A. thaliana miRNA genes contains intron(s). In the majority of intron-containing precursors, the miRNA-enclosing hairpin loop structure is located within the first exon.…”
mentioning
confidence: 99%
See 1 more Smart Citation